Penyuluhan Kesehatan dan Pemeriksaan Glukosa Darah, Kolesterol, Asam Urat, Tekanan Darah pada Lanjut Usia di Karatung II Manganitu Kabupaten Sangihe - Detty Jeane Kalengkongan; Yeanneke Liesbeth Tinungki; Yenny Budiman Makahaghi (I-Com: Indonesian Community Journal, 2025)
The elderly very vulnerable to various life-threatening diseases; stroke, coronary heart disease, diabetes mellitus due to low knowledge about diseases. Elderly also  great challenges in maintaining health to achieve happy old age due to lack awareness conducting health checks. Degenerative diseases increasing and it difficult for elderly to achieve life expectancy. Method implementation is survey, implementation activities, counseling, checking blood pressure, blood sugar, cholesterol, uric acid ending with monitoring, evaluation. Results community service show that number elderly people present is 28 people. Average knowledge is 5, 8. Blood pressure increased> 150 mmHg amounted 2 people, Blood Sugar increased> 120 mg/dl amounted 14 people, Cholesterol increased>235 mg/dl amounted 3 people. The importance of service to the elderly causes knowledge to increase, the elderly can find out the results of checking blood pressure, blood sugar, cholesterol, uric acid. When elderly know results of the examination, elderly have awareness to adopt healthy lifestyle.